DETERMINING THE RELATIONSHIP BETWEEN SOCIAL MEDIA APPEARANCE CONSCIOUSNESS AND SELF-ESTEEM IN ADOLESCENTS - Oluc, Tugba; Ayran, Gulsun (Universitas Airlangga, 2024)
Introduction: Adolescents' active use of social media raises curiosity about how they appear on social media platforms. This situation may cause changes in their personality. This study was conducted to determine the relationship between social media appearance consciousness and self-esteem in adolescents. Method: This cross-sectional study was conducted between January and March 2023. The study involved 1103 students from three different high schools located in a province in eastern Turkey. As part of the study process, data were collected using the